Assessing change in English second language writing performance - Barkaoui, Khaled; Hadidi, Ali, (Professor of linguistics) (New York : Routledge, 2021)
"This book introduces a new framework for analyzing second-language (L2) learners' written texts. The authors conducted a major study on changes and differences in English L2 learners' writing performance to advance understanding of the nature of L2 writing development over time, in relation to L2 instruction and testing, and to offer a model that professionals and researchers can use in their own longitudinal and cross-sectional studies of L2 writing development. Grounded in research, data, theory, and technology, this will be a welcome how-to for language test developers, scholars, and graduate students of (L2) writing and assessment"--
OCLC-licensed vendor bibliographic record.
Keywords: Composition (Language arts) -- Study and teaching (Higher); Composition (Language arts) -- Evaluation; English language -- Rhetoric -- Study and teaching (Higher) -- Foreign speakers; Second language acquisition; LANGUAGE ARTS & DISCIPLINES / Linguistics